Revitalizing vehicle innovation: Exploring electric car chassis structures through finite element analysis - Hafidz Dwi Anggara (Researcher and Lecturer Society, 2024)
The increasing number of motor vehicles contributes significantly to air pollution, resulting in global environmental degradation due to CO2 emissions. Electric cars offer an environmentally friendly solution to this issue. Vehicle chassis plays a critical role as the support structure for various components. This study aims to design an optimal electric vehicle chassis considering weight, safety, and strength aspects, utilizing von Mises stress analysis to assess stress levels and safety factors. The research focuses on determining the chassis' safety factor and stress distribution, employing alloy steel material and subjecting it to a 5000 N force using finite element analysis (FEA). Analysis results show von Mises stress ranging from 0.002 N/mm^2 to 167.549 N/m^2, displacement ranging from 0.000 mm to 1.812 mm, strain ranging from 0.000 to 0.0001, and safety factors ranging from 2.327 to 371,181.531. Consequently, overall simulation on the chassis is targeted to run optimally, which fulfills the objectives of this research.